Dynamics of Nasal Irritation from Pulsed Homologous Alcohols - Wise, Paul M.; Zhao, Kai; Wysocki, Charles J. (Chemical senses, 2010)
Relatively, few studies have focused on how nasal irritation changes over time. To simulate the rhythm of natural respiration, subjects received 3-s pulses of volatile organic compounds interspersed with 3-s pulses of clean air. Each trial, subjects received 9 pulses of a chemical vapor over about 1 min. Subjects rated nasal irritation from each pulse using magnitude estimation. Within a trial, compound and concentration were fixed. Compound (ethanol, n-butanol, or n-hexanol) and concentration (4 levels for each compound) varied across trials. For all stimuli, rated irritation decreased over time (adaptation). Plots of log-rated intensity versus elapsed time were approximately linear (intensity decreased by a fixed ratio per unit time). Interestingly, the slopes of intensity versus time functions differed very little: Regardless of concentration and compound, rated irritation decreased by about 32% over the 9 pulses. The basic mechanism of short-term adaptation may be the same for the 3 alcohols studied. Regardless, these data suggest that very simple models might be able to describe some aspects of perceptual dynamics quite well.